1986
DOI: 10.3109/17453678608994374
|View full text |Cite
|
Sign up to set email alerts
|

Occupation after hip replacement for arthrosis

Abstract: After hip replacement for primary arthrosis, 69/104 patients younger than 60 years returned to work within 2 years. Long preoperative sick leave increased the risk of both retirement and long postoperative sick leave. The retirement rate was also influenced by occupation, whereas sex, age, or bilateral operations had no influence on postoperative retirement nor on postoperative sick leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 6 publications
3
54
1
1
Order By: Relevance
“…The prognosis for returning to work after hip and back surgery is poor for patients with a preoperative disability pension (Jensen et al 1985, Johnsson and Persson 1986, Jonsson and Stromqvist 1994, and we found the same after knee replacement. This might be explained by progressive impairment in work motivation induced by the disability pension-an explanation in accordance with our results in the NHP part of the investigation, where patients on partial or complete disability pension showed impairment in the psychological categories but not in the physical capacity categories.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The prognosis for returning to work after hip and back surgery is poor for patients with a preoperative disability pension (Jensen et al 1985, Johnsson and Persson 1986, Jonsson and Stromqvist 1994, and we found the same after knee replacement. This might be explained by progressive impairment in work motivation induced by the disability pension-an explanation in accordance with our results in the NHP part of the investigation, where patients on partial or complete disability pension showed impairment in the psychological categories but not in the physical capacity categories.…”
Section: Discussionsupporting
confidence: 70%
“…Information is sparse about the influence of preoperative working status on social rehabilitation after knee prosthetic treatment. In a previous study of total hip replacement for arthrosis (Johnsson and Persson 1986), the occupations of 118 patients who were below the age of 60 years at surgery was investigated. 69 patients returned to work and, as in our study, the risk of long postoperative sick-leave or postoperative pension increased with the duration of preoperative sick leave.…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated significant positive results in the improvement of muscle strength force in the intervention group compared with the nonintervention group, and these findings were similarly highlighted by Husby et al [33] in another randomized study. Even with good outcomes in the muscle strength force as measured by Kendall's criteria [22], this method may be imprecise when compared with a previously described method using a dynamometer, an instrument that is thought to have higher measurement accuracy [26,28,37]. Kendall's criteria [22] can be incorrect due to the negative influence of the patient's pain as well as due to measurements obtained by different researchers.…”
Section: Discussionmentioning
confidence: 97%
“…In a systematic review, Minns Lowe et al indicated a lack of a standard method among researchers for the measurement of muscle strength [38]. In fact, some authors use manual measurement [39][40], while others use a dynamometer [26,28,37]. Even those who use a dynamometer often measure the strength of different muscle groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that quality of life decreases and pain increases while waiting for surgery [49][50][51][52][53][54]. In addition to quality of life consequences, there are social consequences to waiting for TJR surgery including reduced or modified work [50,55,56], prolonged pre-and post-operative sick leave, job loss, and a reduced possibility of returning to work post-operatively [55][56][57]. Patients who wait longer for surgery are less likely to ever return to work even when the most severe patients receive surgery first [55].…”
Section: Introductionmentioning
confidence: 99%